EXPERIMENTAL STUDY OF NOCARDIOSIS IN GUINEA PIGS - ALWAN, M. J. (The Iraqi Journal of Veterinary Medicine, 2000)
The pathology of local isolated strain of Nocardia asteroides was study in pigs . 60 animals were divided into two groups. The 1st group (40 animals) was given a single intrapulmonary of 3.3X10’CFU of N. astoroides. The 2 nd group (20 animals) served as control . Eight animals died during the first 3 weeks post – infection while the remaining were sacrificed at 6, 12, 24, 48 hrs and 4, 8, 16, 24 and 62 days P.I. Early pathological examination revealed acute suppurative changes which seen turned into disseminated chronic form. Pyogranul matous and epithelioid granuloma have represented the main pathological changes at 8-24 days P.J. The results revealed arisein the level of bacterial counts followed by drop in count within 8-24 days P.I. Excepted kidney in which high bacterial counts persisted toward the end of the experiment